Global burden of road traffic accidents in older adults: A systematic review and meta-regression analysis. (September 2017) - Ang, Boon Hong; Chen, Won Sun; Lee, Shaun Wen Huey
Highlights: There is limited evidence on the best mortality predictor in older adults following RTA. One in every 6 older adults involved in a RTA will die. Pedestrians and very elderly adults (≥75 years) have higher mortality rates. An urgent need for guidelines specific for older adults in LMIC. Abstract: Purpose of the study: This study aims to estimate the burden of road traffic accidents and death among older adults. Design and methods: A systematic literature review was conducted on 10 electronic databases for articles describing Road Traffic Accident(RTA) mortality in older adults until September 2016. A random-effects meta-regression analyses was conducted to estimate the pooled rates of road traffic accidents and death. Results: A total 5018 studies were identified and 23 studies were included. Most of the reported older adults were aged between 60 and 74 years, with majority being male gender and sustained minor trauma due to Motor-Vehicle Collision (MVC). The overall pooled mortality rate was 14% (95% Confidence Interval, CI: 11%, 16%), with higher mortality rates in studies conducted in North America (15%, 95% CI: 12%, 18%) and older adults admitted to trauma centers (17%, 95% CI: 14%, 21%). Secondary analysis showed that the very elderly adults (aged >75 years) and pedestrians had higher odds of mortality death (Odds Ratio, OR: 2.05, 95% CI: 1.25, 3.38; OR: 2.08, 95% CI: 1.63, 2.66, respectively). Implication: A new comprehensive trauma management guidelines tailored to older adults should be established in low and middle-income countries where such guidelines are still lacking.